Transcatheter Embolization for Giant Splenic Artery Aneurisms: Still an Open Question - Marianna Mastroroberto; Sonia Berardi; Matteo Renzulli; Caterina Maggioli; Paolo Pianta; Antonio Daniele Pinna; Rita Golfieri; Claudia Sama (Case Reports in Radiology)
Transcatheter embolization is the mainstay of the therapy of splenic artery aneurysms (SAAs) in patients with portal hypertension. It is indicated when the SAA diameter reaches 20 mm. Although endovascular techniques are effective and safe for the treatment of medium-sized SAAs, little is known about their applicability to large-sized SAAs. Herein, we report a case of giant SAA, which was treated with transcatheter coil embolization. The case was not considered suitable for surgery because of the presence of severe portal hypertension. The procedure was complicated by bacterial infection of the coils within the aneurismatic sac, leading to the development of hepatic failure. A liver transplant was then successfully performed despite the presence of a nonresponsive infection.